THE ROLE OF PSYCHODIAGNOSTICS IN MEASURING AND UNDERSTANDING PSYCHOLOGICAL CONDITIONS - Putri Damayati, Eka; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
Psychodiagnostics is a crucial tool in psychology, used to measure, assess, and understand an individual's psychological state. The primary goal of psychodiagnostics is to provide an objective picture of a person's cognitive, emotional, and behavioral aspects, which can be used as a basis for intervention, counseling, and research. This article examines the role of psychodiagnostics in understanding psychological conditions through various methods, including standardized psychological tests, observation, clinical interviews, and personality inventories. The study's findings indicate that the appropriate use of psychodiagnostics can improve the accuracy of assessing psychological disorders, identify individual strengths and weaknesses, and facilitate appropriate intervention planning. However, the application of psychodiagnostics also faces challenges related to tool validity, assessor bias, and the ethical use of psychological data. Therefore, psychodiagnostics serves not only as a measurement tool but also as an important medium for understanding an individual's overall psychological dynamics, thus supporting a more scientific and evidence-based psychological practice.